2022
DOI: 10.1111/tpj.15744
|View full text |Cite
|
Sign up to set email alerts
|

Diversification of SEC15a and SEC15b isoforms of an exocyst subunit in seed plants is manifested in their specific roles in Arabidopsis sporophyte and male gametophyte

Abstract: SUMMARY The exocyst complex is an octameric evolutionarily conserved tethering complex engaged in the regulation of polarized secretion in eukaryotic cells. Here, we focus on the systematic comparison of two isoforms of the SEC15 exocyst subunit, SEC15a and SEC15b. We infer that SEC15 gene duplication and diversification occurred in the common ancestor of seed plants (Spermatophytes). In Arabidopsis, SEC15a represents the main SEC15 isoform in the male gametophyte, and localizes to the pollen tube tip at the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Are core subunits of embryophyte exocyst functionally conserved [102] and how do they contribute to the overall land plant evolution as indicated e.g. for SEC15a versus SEC15b in seed plants or EXO70A1 vs. EXO70A2 in Angiosperms [103,104]?…”
Section: Plant Exocyst Complex In Defense Against Pathogens and In Sy...mentioning
confidence: 99%
See 1 more Smart Citation
“…Are core subunits of embryophyte exocyst functionally conserved [102] and how do they contribute to the overall land plant evolution as indicated e.g. for SEC15a versus SEC15b in seed plants or EXO70A1 vs. EXO70A2 in Angiosperms [103,104]?…”
Section: Plant Exocyst Complex In Defense Against Pathogens and In Sy...mentioning
confidence: 99%
“…NBR1 (receptor for selective autophagy) accumulates during Pseudomonas syringae infection (i.e. is not degraded) and participates in the defense responses [103]. During Phytophtora infestants infection, host plant NBR1/ ATG8-positive authophagosomes are targeted to the haustorium-plant interface to limit pathogen haustoria growth [106] and, in Blumeria graminis infection, EXO70B2 participates in papillae and encasement formation [109].…”
Section: Plant Exocyst Complex In Defense Against Pathogens and In Sy...mentioning
confidence: 99%
“…For example, immunofluorescence assays showed that SEC6 and SEC8 were localized at the tip of the tobacco pollen tube (Hála et al, 2008). SEC8 and SEC15a were localized at the pollen tube tip and plasma membrane in Arabidopsis (Bloch et al, 2016; Batystová et al, 2022). However, the localization of SEC5 in the pollen tube has not been reported thus far.…”
Section: Introductionmentioning
confidence: 99%